OGLE-2014-BLG-1112LB: a microlensing brown dwarf detected through the channel of a gravitational binary-lens event - Han, Cheongho; Jørgensen, Uffe G. (The astrophysical journal, 2017)
Due to the nature of the gravitational ﬁeld, microlensing, in principle, provides an important tool for detecting faint and even dark brown dwarfs. However, the number of identiﬁed brown dwarfs is limited due to the difﬁculty of the lens mass measurement that is needed to check the substellar nature of the lensing object. In this work, we report a microlensing brown dwarf discovered from an analysis of the gravitational binary-lens event OGLE-2014-BLG1112. We identify the brown dwarf nature of the lens companion by measuring the lens mass from the detections of both microlens-parallax and ﬁnite-source effects. We ﬁnd that the companion has a mass of (3.03  0.78) ´ 10-2 M and it is orbiting a solar-type primary star with a mass of 1.07  0.28 M. The estimated projected separation between the lens components is 9.63±1.33 au and the distance to the lens is 4.84±0.67 kpc. We discuss the usefulness of space-based microlensing observations for detecting brown dwarfs through the channel of binary-lens events.